Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine - Mei-Rong Zhang; Kan Jiang; Jun-Li Yang; Yan-Ping Shi (Natural Product Research, 2020)

Natural products development under epigenetic modulation in fungi - Chi-Ying Li; Yu-Ming Chung; Yang-Chang Wu; Attila Hunyadi; Clay C. C. Wang; Fang-Rong Chang (Phytochemistry Reviews, 2020)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

High-frequency compensation for seismic data based on adaptive generalized S transform - Hui-Feng Li; Jin Wang; Zheng-Rong Wei; Fei-Long Yang (Applied Geophysics, 2020)

Inverse gaussian beam stack imaging in 3D crosswell seismic exploration of deviated wells and Its application - Fei-Long Yang; Chong Zhao; Zheng-Rong Wei; Hui Sun; Hui-Feng Li; Chi Zhao; Hao Luo (Applied Geophysics, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

PSD-93 Interacts with SynGAP and Promotes SynGAP Ubiquitination and Ischemic Brain Injury in Mice - Qingxiu Zhang; Hui Yang; Hong Gao; Xiaomei Liu; Qingjie Li; Rong Rong; Zhenqian Liu; Xiu-e Wei; Liping Kong; Yun Xu; Liangqun Rong (Translational Stroke Research, 2020)

Quantitative Angiographic Hemodynamic Evaluation After Revascularization Surgery for Moyamoya Disease - Yu Chen; Li Ma; Shuo Yang; Jan-Karl Burkhardt; Junlin Lu; Xun Ye; Weijian Jiang; Zeguang Ren; Rong Wang; Xiaolin Chen; Yuanli Zhao (Translational Stroke Research, 2020)
The corresponding hemodynamic changes of the internal carotid artery (ICA) after the revascularization surgery for moyamoya disease (MMD) remain unclear. The aim of this study was to analyze the hemodynamic changes of the ipsilateral ICA after the combined direct and indirect extracranial-intracranial (EC-IC) bypass. MMD patients undergoing combined EC-IC bypass were retrospectively reviewed. The mean transit time (MTT) of ICA was evaluated by color-coding angiography before revascularization and at follow-up. The MTT defined as the blood transit time between the end of cervical portion (C1) and the C7 segment of ICA. The clinical prognosis was assessed with Matsushima grading system, moyamoya vessel reduction system, and modified Rankin Scale (mRS). The correlation between hemodynamic parameter and prognosis was analyzed. Subgroup analysis was conducted between different presentations and different ages. Fifty-one patients were identified and the mean imaging follow-up interval was 5.5 months. The ICA-MTT was increased after the combined revascularization ( P < 0.001) compared with contralateral ICA. Faster preoperative ICA-MTT was significantly associated with improved mRS in the ischemic group ( P = 0.05). The increased ICA-MTT was significantly associated with favorable neoangiogenesis ( P = 0.04), moyamoya vessel reduction (> 50%) ( P = 0.023), and improved mRS score ( P = 0.008). In subgroup analysis, the correlation in the ischemic subgroup and adult subgroup remained significant. In this cohort, the ICA-MTT increased after the combined EC-IC bypass, and there was a positive correlation between the increased blood transit time and favorable outcomes. Color-coding DSA proved to be useful as a quantitative and serial method to monitor postoperative courses after revascularization in MMD.

ERas regulates cell proliferation and epithelial–mesenchymal transition by affecting Erk/Akt signaling pathway in pancreatic cancer - Yang Liu; Peng Qin; Rong Wu; Lianfang Du; Fan Li (Human Cell, 2020)
Pancreatic cancer is the fourth most common lethal malignancy with an overall 5-year survival rate of less than 5%. ERas, a novel Ras family member, was first identified in murine embryonic stem cells and is upregulated in various cancers. However, the expression and potential role of ERas in pancreatic cancer have not been investigated. In this study, we found that ERas mRNA and protein were upregulated in pancreatic cancer tissues and cells compared with controls. Knockdown of ERas in pancreatic cancer cells by siRNA significantly decreased cell proliferation, colony formation, migration, and invasion and promoted cell apoptosis in vitro. Epithelial–mesenchymal transition (EMT) is closely related to tumor progression. We observed a significant decrease in N-cadherin expression in pancreatic cancer cells in response to ERas gene silencing by immunofluorescence assay and western blot. Furthermore, tumor growth and EMT were inhibited in xenografts derived from pancreatic cancer cells with ERas downregulation. We further investigated the regulatory mechanisms of ERas in pancreatic cancer and found that ERas may activate the Erk/Akt signaling pathway. Moreover, Erk inhibitor decreased pancreatic cancer cells proliferation and colony formation activities. Our data suggest that targeting ERas and its relevant signaling pathways might represent a novel therapeutic approach for the treatment of pancreatic cancer.

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Heat-air-moisture coupled model for radon migration in a porous media - Yu Cui; Shengyang Feng; Puxin Chen; Yongjun Ye; Yurong Wu; Ce Li; Rong Yang; Hong Wang (Environmental Science and Pollution Research, 2020)

Molecular Characterization and Promoter Analysis of Novel Sugar Transporter Gene ScERD6 in Sugarcane - Xiao-Rong Miao; Xu-Peng Zeng; Jun-Qi Niu; Aamir Mahmood; Li-Tao Yang; Bao-Qing Zhang; Yang-Rui Li (Sugar Tech, 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

New Terpenoids And Lignans From The Twigs Of T ripterygium Hypoglaucum - Hui Zheng; Li Wang; Tao Yang; Dan Liu; Hong-Mei Li; Xuan-Qin Chen; Rong-Tao Li (Natural Product Research, 2020)

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Bergaptol, a mechanism-based inactivator of CYP2C9 - Tingting Jiang; Ting Cheng; Jing Li; Mengyue Zhou; Rong Tan; Xiaojing Yang; Yang Wang; Weiwei Li; Jiang Zheng (Medicinal Chemistry Research, 2020)

GDP: an open-source GNSS data preprocessing toolkit - Zhengsheng Chen; Yang Cui; Linyang Li; Qinghua Zhang; Zhiping Lu; Xuerui Li; Yingcai Kuang; Kaichun Yang; Fengjuan Rong (GPS Solutions, 2020)

A study on the effects of salinity and pH on PSII function in mulberry seedling leaves under saline–alkali mixed stress - Zhang Huihui; Li Xin; Che Yan-hui; Wang Yue; Li Ma-bo; Yang Rong-yi; Xu Nan; Sun Guang-yu (Trees, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

PI3K/Akt pathway is involved in the activation of RAW 264.7 cells induced by hydroxypropyltrimethyl ammonium chloride chitosan - Yue Yang; Rong’e Xing; Song Liu; Yukun Qin; Kecheng Li; Huahua Yu; Pengcheng Li (Journal of Oceanology and Limnology, 2020)

The Diversity of Associated Microorganisms in Different Organs and Rhizospheric Soil of Arctium lappa L. - Yanping Xing; Yanyun Yang; Liang Xu; Ning Hao; Rong Zhao; Jiahao Wang; Shengnan Li; Dachuan Zhang; Tingting Zhang; Tingguo Kang (Current Microbiology, 2020)

Polymer-coated urea effects on maize yield and nitrogen losses for hilly land of southern China - Yong Xie; Li Tang; Lan Yang; Yuping Zhang; Haixing Song; Chang Tian; Xiangmin Rong; Yongliang Han (Nutrient Cycling in Agroecosystems, 2020)

Decrypting the crosstalk of noncoding RNAs in the progression of IPF - Yujuan Wang; Han Xiao; Fenglian Zhao; Han Li; Rong Gao; Bingdi Yan; Jin Ren; Junling Yang (Molecular Biology Reports, 2020)
Idiopathic pulmonary fibrosis (IPF) is an agnogenic, rare, and lethal disease, with high mortality and poor prognosis and a median survival time as short as 3 to 5 years after diagnosis. No effective therapeutic drugs are still not available not only in clinical practice, but also in preclinical phases. To better and deeper understand pulmonary fibrosis will provide more effective strategies for therapy. Mounting evidence suggests that noncoding RNAs (ncRNAs) and their interactions may contribute to lung fibrosis; however, the mechanisms underlying their roles are largely unknown. In this review, we systematically summarized the recent advances regarding the crucial roles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and circular RNAs (circRNAs) and crosstalk among them in the development of IPF. The perspective for related genes was well highlighted. In summary, ncRNA and their interactions play a key regulatory part in the progression of IPF and are bound to provide us with new diagnostic and therapeutic targets.

Circadian gene Clock participates in mitochondrial apoptosis pathways by regulating mitochondrial membrane potential, mitochondria out membrane permeablization and apoptosis factors in AML12 hepatocytes - Shuhong Yang; Yanyou Liu; Yimei Guo; Rong Liu; Fang Qi; Xiaoxue Li; Hang Yu; Shuting Cheng; Zhengrong Wang (Molecular and Cellular Biochemistry, 2020)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

The Monitoring of the Pollution Degree of Maize Under Copper Stress - Chao Zhang; Keming Yang; Kunpeng Rong; Feng Cheng; Yan Li (Journal of the Indian Society of Remote Sensing, 2020)

Utilization of pre-existing competent and barren quartz veins as hosts to later orogenic gold ores at Huangjindong gold deposit, Jiangnan Orogen, southern China - Liang Zhang; David I. Groves; Li-Qiang Yang; Si-Chen Sun; Roberto F. Weinberg; Jiu-Yi Wang; Sheng-Gang Wu; Lei Gao; Lan-Ling Yuan; Rong-Hua Li (Mineralium Deposita, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Spectral Characteristics and the Study of Pollution Degree of Maize Leaves Under Copper and Lead Stress - Chao Zhang; Keming Yang; Yan Li; Feng Cheng; Kunpeng Rong (Journal of the Indian Society of Remote Sensing, 2020)

Effects of topography on dynamic responses of single piles under vertical cyclic loading - Li-ming Qu; Xuan-ming Ding; Chong-rong Wu; Yong-hong Long; Jin-chuan Yang (Journal of Mountain Science, 2020)

Antler stem cells as a novel stem cell source for reducing liver fibrosis - Xiaoli Rong; Yanyan Yang; Guokun Zhang; Haiying Zhang; Chunyi Li; Yimin Wang (Cell and Tissue Research, 2020)
Liver fibrosis results from collagen fiber deposition. Antler stem cells (ASCs) naturally in vivo differentiate into cartilage, which is only made of Col II in collagen component; whereas liver fibrosis is caused by over-abundance of Col I and III. In addition, ASCs can effectively promote regenerative wound healing in which tissue contains very few collagen fibers (Col I). In this study, we investigate the therapeutic effects of ASCs in a rat model of CCl 4 -induced liver fibrosis. Rats were treated with ASCs for 4 weeks in vivo, then biochemical and histopathological analyses were performed. Furthermore, we established cell co-culture systems of hepatic stellate cells (HSCs) and ASCs and of M1 macrophages and ASCs in vitro. Mesenchymal stem cells (MSCs) were used as a positive control. The results showed that ASC transplantation alleviated liver fibrosis effectively as evidenced by reduced collagen accumulation, decreased fatty degeneration, increased hepatocyte regeneration, decreased inflammation and significantly enhanced liver function; moreover, ASCs decreased the expression of pro-fibrogenic factors including TGF-β and α-SMA. Additionally, our study showed that ASCs inhibit HSC activation and proliferation by controlling the expression of MMPs, TIMP1, TGF-β, α-SMA and COL1A2 involved in these processes. Our results suggested that ASCs alleviate liver fibrosis effectively and inhibit HSC activation. Thus, ASCs may serve as a novel stem cell source for the treatment of liver fibrosis in the clinic.

Three functional variants were identified to affect RPS24 expression and significantly associated with risk of colorectal cancer - Danyi Zou; Hongli Zhang; Juntao Ke; Jiaoyuan Li; Ying Zhu; Yajie Gong; Yang Yang; Jianbo Tian; Yi Zhang; Xiating Peng; Kailin Cai; Rong Zhong; et al. (Archives of Toxicology, 2020)